Constructivist Liveworksheet in Two Variabel Linear Equation System - Priwantoro, Soffi Widyanesti; Fahmi, Syariful; Fitrian, Ressa (Jurnal Pendidikan Matematika Unpatti, 2025)
This research was motivated by problems identified during the preliminary research at SMP Muhammadiyah 1 Godean through interviews with the mathematics teacher and the distribution of questionnaires to students. The information obtained indicated that mathematical problems in the form of story problems were difficult to understand and there was a lack of mathematical learning media that used a specific approach to help students understand mathematical problems. Therefore, this study aims to develop and evaluate the feasibility of an electronic student worksheet based on a constructivist approach using Liveworksheets for the topic of Systems of Linear Equations in Two Variables (SPLDV) for Grade VIII students. This research used a Research and Development (R&D) method using the ADDIE model. The research subjects were students of class VIII-D. The validation process was carried out by two validators, namely media and subject matters validators. After the validation assessment was completed, a trial was conducted, consisting of a small-scale trial and a large-scale trial. Based on data analysis, the research result indicate that electronic worksheet received a very good rating from both the subject matter expert with a score of 110 and the media expert with a score 89. Student responses were also categorized as good, with a score of 97.7 in the small group trial and 96.6 in the large group trial. Thus, the developed electronic worksheet is deemed feasible for use in mathematics learning.